Strategi Ibu dengan Peran Ganda dalam Membentuk Kemandirian Anak Usia Pra Sekolah - Ervin Nurul Affrida (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2017)
This study aims for understand mothers experience with dual role to establish of independence child. Mother with dual role interpreted as a mother become housewife and work. The existence of dual role make the role as a mother divided by the role as a career woman. Especially if the child has entered pre-school age, the role of mother is needed because at this stage the child get in golden periode, window of opportunity, and critical period (Depker, 2010). One of the skills that should be developed is independence that became one of the goals of character education. Especially for working mothers, establishing independence of children from an early age can help children to perform simple daily activities when the mother at work. The study participants were four mothers with dual roles and have children with 3-6 year olds attending Play Group/Kindergarten Program. Data collection using in-depth interview then analyzed by Interpretative Phenomenological Analysis (IPA) method. The result of the research shows that the mother experience with dual role in forming the independence of the children use of parenting, giving examples and mentoring to doing activities independently, and familiarize the children to perform simple daily activities to supply needs self.